Community-based vicuña (Vicugna vicugna) shearing in the arid Puna of Argentina: Body weight and fiber traits obtained during the chakus - Sacchero, Diego Mariano (2022)
In the Argentine Puna, innovation proposals for the production of vicuña fiber represent a strategic opportunity for local communities. However, the development of these proposals, essential for the addition of local value, is affected by the lack of information on the relationship between fiber quality and processing. Thus, this study aimed to characterize the variability in both the quantity and quality of vicuña fiber obtained by shearing in the Argentine Puna, in the context of sustainable management plans presented by different indigenous communities of the Yavi district, Jujuy province. Samples (n = 150) were taken during shearing in locations at low (<3814 masl, n = 5) and high altitude (>4222 masl, n = 4). The following were recorded: sex, age, and body weight (BW, kg) of the animals, fleece weight (FW, g), staple length (SL, mm), mean fiber diameter (MFD, μm), mean diameter of down fibers (DDO, μm), mean diameter of hair (DHA, μm), coarse hair content (CHC, %), proportion of down fibers (PWB, %) and mean fiber curvature (MFC, ◦/mm). In adult vicuñas BW and SL were significantly affected by altitude, FW was affected by sex, and all the other quality variables were affected by the sampling location. Adult vicuñas BW from high locations were lighter than those from low locations (38.6 vs. 41.6 kg, P < 0.01). SL was greater in animals from low locations than in those from high locations (42.4 vs. 38.8 mm, P < 0.05). Average FW was 228 g, with animals from low locations showing more variable FW than those from high locations. Females produced lighter fleece than adult males (216 vs. 244 g, P < 0.01). MFD, DDO and DHA, CHC, PWB and MFC presented averages of 13 μm, 12.6 μm, 53 μm, 0.9 %, 87.0 % and 87◦/mm, respectively. For young vicuñas, the BW and FW were 30.9 kg and 213 g, respectively. Differences among sampling locations were significant for all quality variables studied and could present implications for the textile processing of vicuña fiber.